Rabies pada Anak: Pencegahan dan Tata Laksana - Tjahjadinata, Christine; Clarita, Wendi (Cermin Dunia Kedokteran, 2024)
Rabies is a fatal zoonotic disease caused by animal bites, with the majority of cases occuring in Asia, including Indonesia. About 30% to 60% of animal bite victims are children under 15 years old. Most rabies deaths are caused by delayed treatment because it is considered harmless, whereas prevention by providing prophylaxis before and after exposure can prevent rabies deaths. Meanwhile, the treatment for rabies is still limited and has a poor prognosis.